Persoalan Kesetaraan Gender dalam Karya Seni Rupa Kontemporer Indonesia - Ira Adriati Winarno (ITB Journal Publisher, LPPM ITB, 2007)
Art work serves not only for personal expression but also have social function. It is quite obvious as some Indonesian women artists use their art works to express gender equality issues. Their ideas are contributing greatly to the development of contemporary visual art in Indonesia. These women artists express issues of gender that whether personally experienced by them or other women in general, using the expressive style of surrealism, expressionism, and naturalism. Certainly, their art works show good aesthetics values, supported by excellent skills and technical abilities. Most of their art works not only provide excellent visualizations but also send strong messages on gender equality issues. Their works, as explained in this study, provide a common ground to increase public awareness for the importance of gender equality issues in Indonesia.